Current approaches for Usher syndrome disease models and developing therapies - Leith, Fiona K.; Lye, Joey; Delaney, Derek S.; McLenachan, Samuel; Chen, Fred K.; Atlas, Marcus D.; Wong, Elaine Y. M. (Frontiers in Cell and Developmental Biology, 2025)
Usher syndrome is a severely debilitating autosomal recessive disorder characterised by congenital or progressive hearing loss, gradual vision loss and in some subtypes, vestibular dysfunction. Much progress has been made in recent years in creating appropriate preclinical models for most subtypes of Usher syndrome to facilitate the development of novel therapies. In this review, we provide an update on new preclinical models of Usher syndrome, with a particular focus on induced pluripotent stem cells and new organoid models. An update on the status of novel therapies is provided, including the development of new genetic therapies using new preclinical models and those currently in clinical trials.